A Study on Educational Technology in Dubai Challenges and Suggested Solutions - Kamel Iran, Hisham Mohammed (2011)
The purpose of this paper is to discuss how education in UAE is better with the presence of technology, how advanced is it now? How it can be better? Worldwide some barriers may arise before integrating high technologies into today's classroom. A couple of the most famous barriers are the cost of software, hardware and the availability of training for teachers, but The UAE government has the financial resources to implement technology at schools and the Ministry of Education in the UAE is striving to keep up with educational standards adopted all over the world. And once H.H. Sheikh Mohammed bin Rashed Al-Maktoom said "Education, Education, Education" while presenting Dubai Strategic Plan 2015 stating that it’s one of his most strategic goals in the UAE development.In line with this trend to integrate information and communication technologies (ICTs) in education, UAE has embraced to use technologies in all educational levels to facilitate learning and teaching, and increase access to learning opportunities.I conducted a survey to examine how education in UAE is better with the implementation of technology from the perspective of both teachers and students from grade 7 to 12 in Dubai’s schools and how it can be even better.The methodology was both qualitative and quantitative as I have done primary research on education technology in other countries and attended an International conference about Information and Communication Technology in Education to have an idea about the current status of educational technology worldwide. Later on, questionnaires were sent out to both Dubai’s students and teachers about technology in education in UAE, 508 valid responses were received and analyzed.New findings within this research show that teachers and students feel that education was improved with the use of technology in education at Dubai’s schools. Teachers and students have the required technological skills and the acceptance to integrate new technologies in education that can add value. Teachers need professional training on how to improve education by technology as well as students need access to different technologies in schools.